Hallazgos ecográficos transperineales en pacientes con incontinencia urinaria de esfuerzo en el Servicio de Ginecología y Obstetricia de un hospital público en el año 2024 - Figueredo Romero, Igor Arturo (2025)
Introduction: Stress urinary incontinence is common. Diagnostic aids are needed to provide objective data to optimize therapeutic strategies. Transperineal ultrasound can be used to evaluate patients with stress urinary incontinence. Objectives: To describe the transperineal ultrasound findings using measurement of urethral neck descent (BND), posterior urethrovesical angle (β angle) at rest and with de Valsalva maneuver, and the presence of bladder neck funneling in patients reporting stress urinary incontinence. Methodology: A descriptive, prospective, cross-sectional study. Transperineal ultrasound measurements were made of bladder neck descent (BND), posterior urethrovesical angle (β angle), and the presence of bladder neck funnelingin patients reporting stress urinary incontinence. Results: A total of 52 patients were included. The mean bladder neck descent (BND) was 10.19 ± 5.2 mm. The mean resting posterior urethrovesical angle (β angle) was 129.27 ± 41.46°. The meanValsalva posterior urethrovesical angle (β angle) was 129.67 ± 38.01°. Bladder neck funneling was present in fourteen (14) of the 52 patients. Conclusion: Transperineal ultrasound provides objective data for the evaluation of patients with stress urinaryincontinence. Further studies with an analytical design are needed to evaluatetransperineal ultrasound in the evaluation of stress urinary incontinence.